Acompañamiento docente para liderar la educación - Incháustegui López, Claudia (2013)
The following article is about the importanceof accompaniment teacher in training,especially in the most distant and neededareas of our country. The author bets forobservation, dialogue and critic-reflectiveperspective that address the teachers totheir better level in the field of learning andcommunication, “for obtain a change in theirmentalities, competences and knowledgethat they impart”